Molecular orbital calculation for the model compounds of kainoid amino acids, agonists of excitatory amino acid receptors. Does the kainoid C4-substituent directly interact with the receptors? - Hashimoto, K.; Matsumoto, T.; Nakamura, K.; Ohwada, S.; Ohuchi, T.; Horikawa, M.; Konno, K.; Shirahama, H. (Elsevier B.V., 2002)
Kainoid amino acids are agonists of the AMPA/kainate receptors and exhibit highly potent neuroexcitatory activity. From the results of extensive structure-activity relationship studies, we previously postulated that the C4-substituent of the kainoid amino acids interacts with an allosteric site of the glutamate receptor with electron-donating character. In order to investigate the mode of action in more detail, molecular orbital calculation for model compounds of the kainoid were performed. The results indicated that the HOMO energy level of the C4-substituent is involved in the potent neuroexcitatory activity, thus supporting our hypothesis. (C) 2002 Elsevier B.V. Ltd. All rights reserved.